2006
DOI: 10.1111/j.1745-7254.2006.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of melanogenesis by scoparone in B16 melanoma cells

Abstract: Aim: The effect of coumarin derivatives on melanogenesis was investigated in B16 murine melanoma cells. Methods: Melanin content and tyrosinase activity were analyzed spectrophotometrically. The expression of tyrosinase, tyrosinaserelated protein-1 (TRP-1) and tyrosinase-related protein-2 (TRP-2) were measured either by reverse transcription-polymerase chain reaction (RT-PCR) or Western blot. Results: Among the coumarin derivatives studied, scoparone (6,7-dimethoxycoumarin) was the most potent; the 6-or 7-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…5,6) Recently, it has been reported that quercetin extracted from herbs, naringenin isolated from citrus, and scoparone from plants stimulate melanogenesis, suggesting that these substances can be used as tanning agents. [7][8][9] In this study, we attempted to identify flavonoids affecting melanogenesis from nobiletin-rich citrus plants native to Jeju island, South Korea. 10) First we examined the effects of the polymethoxylated flavones nobiletin, tangeretin, and sinensetin on melanogenesis (Fig.…”
Section: Involvement Of Extracellular Signal-regulated Kinase In Nobimentioning
confidence: 99%
“…5,6) Recently, it has been reported that quercetin extracted from herbs, naringenin isolated from citrus, and scoparone from plants stimulate melanogenesis, suggesting that these substances can be used as tanning agents. [7][8][9] In this study, we attempted to identify flavonoids affecting melanogenesis from nobiletin-rich citrus plants native to Jeju island, South Korea. 10) First we examined the effects of the polymethoxylated flavones nobiletin, tangeretin, and sinensetin on melanogenesis (Fig.…”
Section: Involvement Of Extracellular Signal-regulated Kinase In Nobimentioning
confidence: 99%
“…The melanin content of the cultured B16 cells were measured as described previously (Yang et al, 2006). The cells were washed twice with PBS and lysed with 20 mM Tris-0.1% Triton X-100 (pH 7.5).…”
Section: Melanin Content Measurementmentioning
confidence: 99%
“…Cellular tyrosinase activity was determined as described previously, 21) with slight modifications. Briefly, the cells were treated with -MSH (100 nM) for 24 h, and then intracellular tyrosinase activity was measured after treatment with various concentrations of [6]-gingerol (0-100 mM) or kojic acid (200 mM) for 24 h. After these treatments, the cells were washed twice with phosphate-buffered saline and homogenized with 50 mM PBS (pH 7.5) buffer containing 1.0% Triton X-100 and 0.1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%